THEORETICAL BASES OF ITERATIVE METHODS OF OPTIMIZATION OF STEADY DECISIONS OF RETURN PROBLEMS GRAVIMETRY AND A MAGNETOMETRY - Minenko, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Working out of the theory of an iterative method for the decision of a return problem gravimetry and a magnetometry is executed and on its base the structure of the formula of the iterative amendment to physical parameter which is optimized together with iterative factor is specified. Are thus considered fields on two adjacent iterations that provides more effective differentiated or general suppression of different classes of errors of measurement of a field and introduction at it different amendments are nonviscous. More exact formula is developed for the account in the iterative amendment of a return matrix. Methods of optimization with the new iterative amendment to physical parameter give more objective restoration of a field which is shown in the form of more flat deflections and breaks of isolines on cards and cuts of abnormal density and intensity of magnetization of rocks at much smaller quantity of the small closed contours which testifies to better interpretation of a field or it transformation.